Istota strategicznej rachunkowości zarządczej - Nowak, Edward (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper treats of strategy-oriented management accounting, also called strategic management accounting. Different definitions of strategic management accounting have been presented. Consequence of strategic management accounting in management process have been formulated. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 290-295